An Analysis of Marked and Unmarked Themes in Indonesian Legends Texts - Yulianti, Delfita; Roza, Veni (English Education Journal, 2023)
This article examines marked and unmarked themes in Indonesian legend texts at Senior High School students using Haliday’s theory on textual equivalence. The goal of this research is to analyze marked and unmarked themes to begin sentences in the stories. The study of marked and unmarked themes is critical because it reveals how writers structure material to convey meaning effectively within a context. Identifying these themes is important for students because it helps them understand the differences of meaning, emphasis, and narrative flow in texts to improve their reading comprehension and writing skill. This study used a qualitative research method. The information was gathered from two manuscripts transcribed in English: The Legend of Malin Kundang and The Legend of Ndaung Snake. The data were examined using Hallidayan theories. An unmarked theme follows the conventional pattern, typically placing the subject at the beginning. In contrast, a marked theme places less expected elements, such as adverbial phrases or objects, at the beginning to highlight. The result of this study shows that the percentage of marked themes in the texts was 51.17%, compared to 49.83% for unmarked themes. The higher percentage of marked themes matters because the writers stress vital information, give a dramatic effect, or exhibit contrast and nuance that unmarked themes might not express as well. Understanding about thematic patterns in scientific writing can help researchers explain their findings more clearly by emphasizing essential points and making them easy to understand by the audience.